2019
DOI: 10.1016/j.actatropica.2019.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Excito-repellent activity of β-caryophyllene oxide against Aedes aegypti and Anopheles minimus

Abstract:  β-caryophyllene oxide had stronger repellent and irritant effect than DEET  Ae. albopictus was more sensitive to β-caryophyllene oxide than An. dirus while, knockdown responses (37%) were observed in An. dirus exposed to 1% β-caryophyllene oxide in the contact trial.  β-caryophyllene oxide did not show any phototoxic activity.  None of the tested β-caryophyllene oxide induced a significant increase of micronucleated cells with or without metabolic activation.  β-Caryophyllene oxide could be considered as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…b-Caryophyllene has shown repellent activity against Aedes aegypti and Anopheles minimus (Nararak et al, 2019), as well as against Sitophilus granarius (Plata et al, 2018). In the study reported by Parisotto et al (2020), β-caryophyllene acted as a powerful anti-inflammatory agent and demonstrated efficiency in the repair of skin tissue; β-caryophyllene provided anti-inflammatory and antiedemagnetic activity in in vivo tests of acute and chronic inflammation through a series of laboratory tests (De Oliveira-Tintino et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…b-Caryophyllene has shown repellent activity against Aedes aegypti and Anopheles minimus (Nararak et al, 2019), as well as against Sitophilus granarius (Plata et al, 2018). In the study reported by Parisotto et al (2020), β-caryophyllene acted as a powerful anti-inflammatory agent and demonstrated efficiency in the repair of skin tissue; β-caryophyllene provided anti-inflammatory and antiedemagnetic activity in in vivo tests of acute and chronic inflammation through a series of laboratory tests (De Oliveira-Tintino et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The ( E )-caryophyllene, at a lower content (2.35%), was found in the essential oil of the EflB specimen. Studies report that caryophyllene oxide has insecticidal activity against the Aedes aegypt vector, an important vector of diseases such as dengue, zika and chikungunya [ 39 ]. This compound also presents gastroprotective potential [ 40 ] and antiviral potential [ 41 ], as well as potential activity against leishmania [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…aegypti. (USDA strain) and Anopheles minimus (KU strain) mosquitoes, performing better than the commercial repellent N,N-diethyl-meta-toluamide (DEET) (Nararak et al, 2019). Caryophyllene oxide, which is a main component also of the Origanum vulgare L. EO, led to 100 % repellence against Tribolium castaneum (Herbst) beetles when tested at 0.03 mg cm −2 (Kim et al, 2010).…”
Section: Insecticidal Activitymentioning
confidence: 99%